Incorporación en el código de procedimiento penal de una norma para que se faculte la conexión de la red informática del registro civil a la policía judicial del sistema de huellas dactilares previo establecer la responsabilidad penal del sospechoso o procesado. - Condolo Acaro, Jackson Vicente (2013)
This job is for a feasibility study aimed at implementing a rule in the Code of Criminal Procedure to determine the database connection Fingerprint Civil Registry to the Judicial Police, in order to provide the facility to the judicial authorities to establish rapid and effective criminal responsibility in the various crimes. The study begins with an introduction, then an analysis of concepts and doctrine focused on the title of the thesis, is a study concerning the historical evolution of both the Criminal Investigation and the process of the institutions of the Prosecutor and Judicial Police, in the same way it looks to the Constitution of the Republic of Ecuador, the Criminal Procedure Code, the Instructions to the Civil Registry Law Identity Cards and Identification. And a law firm laws as Spain Argentina and the United States of America, likewise is a study focused on determining the importance of fingerprints in criminal investigations, Below is the field study in which it was possible to highlight the importance of fingerprints in criminal investigations as the need to implement a standard probability of a connection computer database of fingerprints to the Civil Registry Judicial Police. Subsequently referred to the conclusions and recommendations reached by the study establish that the investigation was completed, after that my proposal propose reform of the Code of Criminal Procedure. In the next part is set to References used in the process of research, appends the instruments used in the process. Finally the index is outlined that allows a quick overview of the contents of this report.